2009
DOI: 10.1111/j.1349-7006.2009.01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the mitochondrial genome confer resistance of cancer cells to anticancer drugs

Abstract: The majority of cancer cells harbor homoplasmic somatic mutations in the mitochondrial genome. We show here that mutations in mitochondrial DNA (mtDNA) are responsible for anticancer drug tolerance. We constructed several trans-mitochondrial hybrids (cybrids) with mtDNA derived from human pancreas cancer cell lines CFPAC-1 and CAPAN-2 as well as from healthy individuals. These cybrids contained the different mitochondrial genomes with the common nuclear background. We compared the mutant and wildtype cybrids f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 44 publications
3
38
1
Order By: Relevance
“…Similarly, Lee et al (141) found that when evaluating TRAIL-induced apoptosis in SKHep1 hepatoma cells, Ú -cells were more resistant than parental cells to the effects of this cytokine; a different model (HeLa cells treated with photodynamic therapy or adriamycin) also showed resistance to apoptosis in Ú -cells (142). However, these data were in contrast to the observations by Mizutani et al (143), which revealed that cybrids derived from mitochondria were more resistant to CDDP than Ú -cells, an observation which agrees with previously cited results, as well as with data from Mizumachi et al (144) who reported that anthracycline-resistant head and neck cancer cells had a significantly higher mtDNA content. Furthermore, in alternative model systems, photodynamic approaches have revealed increases in cell death with mtDNA depletion (145,146); indeed, in L1210 murine leukemia cells, there was a significant increase in the sensitivity to mitochondriallyrelated photodamage in Ú -cells, a process giving rise to apoptotic death; when made resistant to ddC, CEM lymphoblast cells showed increases in their mtDNA content and expression (126).…”
Section: Targeting the Mitochondria As A Translational Therapeutic Apcontrasting
confidence: 56%
“…Similarly, Lee et al (141) found that when evaluating TRAIL-induced apoptosis in SKHep1 hepatoma cells, Ú -cells were more resistant than parental cells to the effects of this cytokine; a different model (HeLa cells treated with photodynamic therapy or adriamycin) also showed resistance to apoptosis in Ú -cells (142). However, these data were in contrast to the observations by Mizutani et al (143), which revealed that cybrids derived from mitochondria were more resistant to CDDP than Ú -cells, an observation which agrees with previously cited results, as well as with data from Mizumachi et al (144) who reported that anthracycline-resistant head and neck cancer cells had a significantly higher mtDNA content. Furthermore, in alternative model systems, photodynamic approaches have revealed increases in cell death with mtDNA depletion (145,146); indeed, in L1210 murine leukemia cells, there was a significant increase in the sensitivity to mitochondriallyrelated photodamage in Ú -cells, a process giving rise to apoptotic death; when made resistant to ddC, CEM lymphoblast cells showed increases in their mtDNA content and expression (126).…”
Section: Targeting the Mitochondria As A Translational Therapeutic Apcontrasting
confidence: 56%
“…6 In colon cancer, mutations and microsatellite instability (MSI) of the mtDNA have been found in 8%-70% of the investigated cohorts. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Furthermore, mtDNA alterations have been proven as prognostic marker, 6 indicator of resistance to FU-based 6,24 and cisplatin chemotherapy, 24 and characteristic of cancer cells, which can be targeted by next-generation metal-based therapy as the recently published organometallic "half sandwich" compound [Os(η(6)-p-cymene)(4-(2-pyridylazo)-N,N-dimethylaniline)I]PF6. 25 The future potential combined diagnostic function of mtDNA alterations to identify tumor cells, which are resistant to conventional cytotoxic drugs and/or responsive to new therapeutic approaches, requires to elucidate its association with other therapeutic markers, which, for example, are related to proliferation, apoptosis, and the EGFR pathway, and to define preanalytic conditions for reliable diagnostic routine.…”
Section: Introductionmentioning
confidence: 99%
“…The interference of mt-mutations with anticancer therapies [Ohta, 2006;Mizutani et al, 2009] and the use of body fluids (sputum in lung and head-and-neck cancers, or urine in renal and urine-bladder malignancies) for the analysis of mt-mutations from tumor patients avoiding invasive techniques [Jakupciak et al, 2008] are 2 promising fields that remain to be further investigated.…”
Section: Final Remarksmentioning
confidence: 99%